Simon vs. the Homo Sapiens agenda - Albertalli, Becky (Albertalli, Becky. Simonverse., 2015)
"Sixteen-year-old, not-so-openly-gay Simon Spier is blackmailed into playing wingman for his classmate or else his sexual identity--and that of his pen pal--will be revealed"--